Two new species of the tribe Meconematini (Orthoptera: Tettigoniidae: Meconematinae) from Taiwan - Wang, Tao; Chen, Powei; Shi, Fuming (Zootaxa, 2019)
This paper describes two new species of the tettigoniid subfamily Meconematinae from Taiwan, i.e. Phlugiolopsis (Phlugiolopsis?) taiwanensis sp. nov. and Xiphidiopsis (Xiphidiopsis) trifoliata sp. nov., and supplies the descriptions and illustrations.